RNA modifications in cancer - Han Wu; Shi Chen; Xiang Li; Yuyang Li; He Shi; Yiwen Qing; Bohe Shi; Yifei Tang; Zhuoyi Yan; Yang Hao; Dongxu Wang; Weiwei Liu (MedComm)
Abstract RNA modifications are emerging as critical cancer regulators that influence tumorigenesis and progression. Key modifications, such as N6‐methyladenosine (m6A) and 5‐methylcytosine (m5C), are implicated in various cellular processes. These modifications are regulated by proteins that write, erase, and read RNA and modulate RNA stability, splicing, translation, and degradation. Recent studies have highlighted their roles in metabolic reprogramming, signaling pathways, and cell cycle control, which are essential for tumor proliferation and survival. Despite these scientific advances, the precise mechanisms by which RNA modifications affect cancer remain inadequately understood. This review comprehensively examines the role RNA modifications play in cancer proliferation, metastasis, and programmed cell death, including apoptosis, autophagy, and ferroptosis. It explores their effects on epithelial–mesenchymal transition (EMT) and the immune microenvironment, particularly in cancer metastasis. Furthermore, RNA modifications’ potential in cancer therapies, including conventional treatments, immunotherapy, and targeted therapies, is discussed. By addressing these aspects, this review aims to bridge current research gaps and underscore the therapeutic potential of targeting RNA modifications to improve cancer treatment strategies and patient outcomes.